Litter Mass and Nutrient Dynamics in a Transformed Rainforest Ecosystem in Southwestern Nigeria - Ojo, AF; Kadeba, TOS; Kayode, J (Bangladesh Journal of Scientific and Industrial Research, 2011)
Litter mass and nutrient changes were studied in a tropical rainforest after the original vegetation was converted to a monoculture plantation of teak. (Tectona grandis Lim.) in Akure forest reserve in southwestern Nigeria. The amount of litter and macronutrients N, P, K, Ca and Mg in litterfall were determined and qualified. The difference in the mean annual litterfall of 6,688 kg ha-1 yr-1 and 3,774 kg ha-1 yr-1 for the natural forest and plantation respectively are in the ratio 2:1. The mean monthly litterfall was statistically significant at 5% probability level. Except for N, nutrient recycling from litterfall showed no significant difference between the two ecosystems. The relative content of the nutrient elements in the litterfall were in the order Ca>Mg>K>N>P in the plantation. Result showed that even though there was lot in litterfall as a result of the conversion, such was not enough to adversely affect the nutrient level of litter and overall litter nutrient contribution to the ecosystem. Key words: Teak; Litter mass; Macronutrients; Tropical rainforest DOI: 10.3329/bjsir.v45i4.7380 Bangladesh J. Sci. Ind. Res. 45(4), 351-358, 2010